Natación y su influencia en el desarrollo de habilidades motrices de niños y niñas entre 5 a 7 años de edad en la Liga Deportiva cantonal del cantón Quevedo, Provincia de Los Ríos - Murillo Ayala, Carlos Emiliano (2018)
The practice of swimming involves many muscles of the body, it is considered that it keeps the organism in a healthy state. On the other hand, swimming brings all the benefits of all sports. Being a very technical sport discipline, swimming increases flexibility, and promotes coordination and agility. It should not be forgotten that swimming, like most sports, favors socialization. In this case, with an addition: the children acquire notions and capacity for rescue, based on this the present investigation is carried out to determine the incidence of the practice of swimming in the development of motor skills in children of 5 years of age. to 7 years old. For the development of this work was applied a non-experimental, explanatory-descriptive design, with a population of swimmers in the swimming discipline and a sample of 30 athletes and a coach, to whom surveys and interviews were applied, the same After analyzing and discussing the results, it was concluded that it is necessary, among other things, to consider the physical, emotional, age and learning levels of the athletes and relate it specifically to each category and according to the needs and abilities of the athletes. the athletes, proposing a didactic guide for the practice of swimming and the development of motor skills in children from 5 to 7 years of age.